LATS2 Deletion Attenuates Myocardial Ischemia-Reperfusion Injury by Promoting Mitochondrial Biogenesis. (19th August 2021) - Chen, Yi; Liu, Chen; Li, Jiannan; Zhou, Peng; Zhao, Xiaoxiao; Chen, Runzhen; Song, Li; Zhao, Hanjun; Yan, Hongbing
Abstract : Reperfusion therapy is the most effective treatment for acute myocardial infarction, but it can damage cardiomyocytes through a mechanism known as myocardial ischemia/reperfusion injury (MIRI). In this study, we investigated whether the large tumor suppressor kinase 2 (LATS2) contributes to the development of myocardial MIRI by disrupting mitochondrial biogenesis. Our in vitro data demonstrate that cardiomyocyte viability was reduced and apoptosis was increased in response to hypoxia/reoxygenation (H/R) injury. However, suppression of LATS2 by shRNA sustained cardiomyocyte viability by maintaining mitochondrial function. Compared to H/R-treated control cardiomyocytes, cardiomyocytes transfected with LATS2 shRNA exhibited increased mitochondrial respiration, improved mitochondrial ATP generation, and more stable mitochondrial membrane potential. LATS2 suppression increased cardiomyocyte viability and mitochondrial biogenesis in a manner dependent on PGC1 α, a key regulator of mitochondrial metabolism. These results identify LATS2 as a new inducer of mitochondrial damage and myocardial MIRI and suggest that approaches targeting LATS2 or mitochondrial biogenesis may be beneficial in the clinical management of cardiac MIRI.